2022
DOI: 10.1108/ebr-01-2022-0015
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic social change (COVID-19) moderating complexity leadership and organisational adaptability in Zimbabwean SMEs

Abstract: Purpose Major social changes, such as those induced by the COVID-19 pandemic, intensify the need for organisations in Africa to accelerate adaptation. Leadership plays an important role in their organisations’ adaptation. This study focuses on how leaders can build adaptive organisations through appropriate complexity leadership practices by establishing which of these most predict organisational adaptation. The study aims to contribute to dramatic social change (DSC) theory and to empirically confirm conceptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…However, much of the work in this area has primarily discussed surface-level components of the topic, such as the cruciality of leadership, reflections on the actions of leaders, and how leadership impacted the firm-level responses throughout the duration of the pandemic and other disruptions [2,[291][292][293][294][295][296][297][298]. Otherwise, much of the literature discusses how leadership (most commonly, transformational leadership) impacted employee well-being and performance throughout the pandemic [299][300][301][302]. A much smaller sect of the research discusses gendered leadership, particularly focusing on difficulties in female leadership roles and lessons that could be learned from female heads of state [299,303].…”
Section: Leadership (Internal Supply Chain)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, much of the work in this area has primarily discussed surface-level components of the topic, such as the cruciality of leadership, reflections on the actions of leaders, and how leadership impacted the firm-level responses throughout the duration of the pandemic and other disruptions [2,[291][292][293][294][295][296][297][298]. Otherwise, much of the literature discusses how leadership (most commonly, transformational leadership) impacted employee well-being and performance throughout the pandemic [299][300][301][302]. A much smaller sect of the research discusses gendered leadership, particularly focusing on difficulties in female leadership roles and lessons that could be learned from female heads of state [299,303].…”
Section: Leadership (Internal Supply Chain)mentioning
confidence: 99%
“…Otherwise, much of the literature discusses how leadership (most commonly, transformational leadership) impacted employee well-being and performance throughout the pandemic [299][300][301][302]. A much smaller sect of the research discusses gendered leadership, particularly focusing on difficulties in female leadership roles and lessons that could be learned from female heads of state [299,303].…”
Section: Leadership (Internal Supply Chain)mentioning
confidence: 99%
“…This ability can facilitate the establishment of a competitive advantage and bolster superior business performance (Chiappini et al, 2022;Jebran & Chen, 2022;Martinez-conesa et al, 2017;Pansiri, 2008;Yung & Chen, 2018). Adaptability and agility (Chingwena & Scheepers, 2022), driven by strong managerial abilities, have enabled SMEs to respond promptly to rapidly changing market conditions and consumer demands. Those businesses that leveraged their competitive advantage, whether it be in product differentiation, innovation, or efficient supply chain management, were better positioned to withstand the disruptions caused by the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Rodriguez [10] assessed the practices of continuous quality improvement among teacher education institutions in Basilan. Furthermore, a review of extant literature showed that previously suggested predictors of organisational adaptability include: scenario planning [11]; complexity leadership [12]; organisational intelligence and efficiency [13]; locus of control, organisational structure and communication [14]; and career management [15].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the avalanche of studies on organisational adaptability, it has been observed that only a few studies have considered the context of operations improvement function [11] [12] [13] [15]. Therefore, the motivation for this study is to fill the existing contextual gap in extant literature by assessing the nexus between operations improvement function (contingency planning, benchmark-ing and continuous improvement processes) and organisational adaptability, as a means of attenuating the effects of the concomitant challenges of the Petroleum tank farms in South-South, Nigeria.…”
Section: Introductionmentioning
confidence: 99%